2015
DOI: 10.3389/fmicb.2015.00761
|View full text |Cite
|
Sign up to set email alerts
|

Decoding the genetic and functional diversity of the DSF quorum-sensing system in Stenotrophomonas maltophilia

Abstract: Stenotrophomonas maltophilia uses the Diffusible Signal Factor (DSF) quorum sensing (QS) system to mediate intra- and inter-specific signaling and regulate virulence-related processes. The components of this system are encoded by the rpf cluster, with genes rpfF and rpfC encoding for the DSF synthase RpfF and sensor RpfC, respectively. Recently, we have shown that there exist two variants of the rpf cluster (rpf-1 and rpf-2), distinguishing two groups of S. maltophilia strains. Surprisingly, only rpf-1 strains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
52
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(60 citation statements)
references
References 47 publications
5
52
0
3
Order By: Relevance
“…These findings suggest that DSF signaling contributes to the virulence of S. maltophilia . The pleiotropic effects of loss by mutation rpfF are consistent with previous observations in different strains of S. maltophilia and species of Stentotrophomonas such as S. rhizophila , where rpfF mutants have altered biofilm formation, extracellular polysaccharide synthesis and virulence (Alvai et al, 2013; Huedo et al, 2015).…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…These findings suggest that DSF signaling contributes to the virulence of S. maltophilia . The pleiotropic effects of loss by mutation rpfF are consistent with previous observations in different strains of S. maltophilia and species of Stentotrophomonas such as S. rhizophila , where rpfF mutants have altered biofilm formation, extracellular polysaccharide synthesis and virulence (Alvai et al, 2013; Huedo et al, 2015).…”
Section: Resultssupporting
confidence: 90%
“…Our findings thus add to a body of work that indicates a role for cell-cell signaling in the virulence of diverse bacterial pathogens. Furthermore, the work is consistent with recent studies that identify the importance of RpfF proteins and DSF signaling in regulation in other environmental strains of S. maltophilia (Alvai et al, 2013; Huedo et al, 2015). Interference with such signaling processes affords a rational approach to aid the treatment of bacterial infections (Ryan et al, 2015).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These determinants are unique in context of this pathogen's limited virulence that limits its invasive potential in comparison to other evolved pathogens like P. aeruginosa . However, S. maltophilia is increasingly known to employ multifactorial determinants like extracellular proteases (Karaba et al, 2013 ), host cell actin modifiers (MacDonald et al, 2016 ), quorum signaling molecules (Huedo et al, 2015 ), and highly evolved efflux-pumps (Chang et al, 2015 ), which independently or together offer formidable recalcitrance and pathogenic fitness.…”
Section: Discussionmentioning
confidence: 99%
“…However, TCS regulation, one of the central molecular mechanisms potentially targetable by novel antibacterial agents, lacks proper investigation in S. maltophilia. Indeed, only HK RpfC, which is responsible for regulating cell-cell communication and virulence factor expression in the close-relative bacteria Xanthomonas spp., has been shown to control diffusible signaling factor (DSF)-triggered modulation in S. maltophilia (14)(15)(16). Our previous study identified FsnR, an orphan RR that controls transcription of flagellar genes and biofilm formation (17), but the cognate HK for FsnR remains unclear.…”
mentioning
confidence: 99%